Cardiac vagal tone as a novel screening tool to recognize asymptomatic cardiovascular autonomic neuropathy: Aspects of utility in type 1 diabetes. (December 2020) - Wegeberg, Anne-Marie; Lunde, Elin D; Riahi, Sam; Ejskjaer, Niels; Drewes, Asbjørn M; Brock, Birgitte; Pop-Busui, Rodica; Brock, Christina
Highlights: Cardiovascular autonomic neuropathy is primarily asymptomatic, thus underrecognized. Reflex tests are standard for diagnosing cardiovascular autonomic neuropathy. Simpler methods to aid clinical recognition and evaluate management are needed. Cardiac vagal tone is sensitive to diagnose cardiovascular autonomic neuropathy. It may provide a cheap, accessible, and easily clinically applicable screening method. Abstract: Aims: To test the performance of the cardiac vagal tone (CVT) derived from a 5-minute ECG recording compared with the standardized cardiovascular autonomic reflex tests (CARTs). Methods: Cross-sectional study included 56 well-phenotyped adults with type 1 diabetes (19–71 years, 2–54 years disease-duration). Autonomic testing included: standardized CARTs obtained with the VAGUS™, CVT, and indices of heart rate variability (HRV) obtained at 24- and 120-hour, and electrochemical skin conductance assessed with SUDOSCAN®. ROC AUC and cut-off values were calculated for CVT to recognize CAN based on ≥ 2 ( established CAN, n = 7) or 1 ( borderline CAN, n = 9) abnormal CARTs and compared to HRV indices and electrochemical skin conductance. Results: Established CAN: The cut-off CVT value of 3.2LVS showed 67% sensitivity and 87% specificity ( p = 0.01). Indices of HRV at either 24-hour (AUC > 0.90) and 120-hour (AUC > 0.88) performed better than CVT. Borderline CAN: The cut-off CVT value of 5.2LVS indicated 88% sensitivity and 63% specificity ( p = 0.07). CVT performed better than HRV indices (AUC < 0.72). Electrochemical skin conductance (AUC:0.63–0.72) had lower sensitivity and specificity compared with CVT. Conclusions: Implementation of CVT with a clinically applicable cut-off value may be considered a quicker and accessible screening tool which could ultimately decrease the number of unrecognized CAN and initiate earlier prevention initiatives.